Prevalence of idiopathic osteosclerosis on cone beam computed tomography images - Azizi, Zeynab; Mosafery, Hosein; Safi, Yaser; Dabirzadeh, Saivash; Vasegh, Zahra (Journal of Dental School, 2019)
Objectives This study was performed to investigate the prevalence of idiopathic osteosclerosis on cone beam computed tomography (CBCT) images of patients. Methods In this descriptive, cross-sectional study, 240 CBCT scans of patients (125 women, 115 men) referred to a private oral and maxillofacial radiology clinic in Tehran in 2013 were selected and evaluated. Presence of idiopathic osteosclerosis and its features including its location in the jaw, its association with teeth, presence or absence of root resorption, number, shape and size of lesions and age and gender of patients were assessed. Descriptive statistics were reported. Chi-square test and independent t-test were used for statistical analysis. Results Idiopathic osteosclerosis was seen on CBCT images of 20 patients (8.33%). The lesion was more frequent in women than men, but the difference was not significant (P = 0.50). Also, the lesion was more common in the mandible than the maxilla (95.6% vs. 4.4%). Most lesions were observed in the molar (56.5%) and premolar (34.7%) areas of the lower jaw. Most lesions did not have any association with teeth (73.9%). More than half of the lesions (56.5%) were round in shape and the rest (43.4%) were irregular. The mean size of the lesions was 5.4 ± 1.8 and 5.7 ± 1.4 mm in the mesiodistal and superior-inferior aspects, respectively. Conclusion The prevalence of idiopathic osteosclerosis of the jaws on CBCT images of an Iranian population was within the range reported by other studies. The lesions were more common in the mandibular molar region with no relation to teeth.